Case Report: Clinical Description of a Patient Carrying a 12.48 Mb Microdeletion Involving the 10p13–15.3 Region - Pan, Yu-qing; Fu, Jian-hua (Frontiers in Pediatrics, 2021)
Partial deletion of 10p chromosome is a rare chromosomal aberration. Submicroscopic deletion of 10p15.3 is mainly related to cognitive deficits, speech disorders, motor delay, and hypotonia with the deleted region ranging from 0.15 to 4 Mb. The clinical phenotype is mainly determined by the ZMYND11 and DIP2C genes. Here we report a rare case of feeding difficulties, hypocalcemia, and psychomotor retardation. Our patient has a 12.48 Mb deletion in 10p15.3-10p13, which is the second case of large 10p deletion among reported cases thus far.